Factores predictores de inicio y cesación de tabaquismo en una cohorte de mujeres chilenas con 5,5 años de seguimiento - Puschel, Klaus (2009)
BACKGROUND: Chilean women have one of the highest smoking prevalence in the world. AIM: To estimate the main factors associated with smoking initiation and quitting among a cohort of adult women living in a low socioeconomic status area of Santiago, Chile. MATERIAL AND METHODS: A random population-based sample of 1,100 women, 18 years and older, were selected from a community located in the South East area of Santiago. Sociodemographic, as well as smoking, beliefs, behaviors, stages of change and nicotine addiction level were recorded during a personal interview. After an average follow-up period of 5.5 years, women were re-evaluated. RESULTS: Seventy-three percent of women completed the study. At baseline, 39% of women were smokers. At the end of the study, there was an absolute smoking rate reduction of 7.1% (p<0.001). The main variables associated with smoking initiation were younger age (Odds ratio (OR): 1.08, 95% confidence intervals (CI): 1.05–1.12), higher education level (OR: 1.2, 95% CI: 1.07–1.35), and having fewer children (OR: 1.3 95% CI: 1.01–1.66). Factors related with quitting were younger age of onset (OR: 1.06 95% CI: 1.02–1.1), higher level of nicotine dependence (OR: 4.22, 95% CI: 1.74–10.27), and higher perception of smoking addiction (OR: 4.34, 95% CI: 2–9.09). Stage of change was associated with smoking cessation but its effect was diluted after adjusting for the level of nicotine addiction. CONCLUSIONS: Sociodemographic and family factors were the main variables related with initiation, whereas age of onset, belief of addiction, and nicotine dependence were the main factors related with cessation. Women with a high motivation for quitting should be evaluated for nicotine addiction level to define the best strategy for intervention (Rev Méd Chile 2009; 137: 1001–9).